Analysis of the relationship between Government spending compression and the window of the currency and its impact on the exchange rate of the Iraqi dinar - عبد اللطيف عماد محمد علي; خليل زهراء فارس (Journal of Economics and Administrative Sciences, 2019)
The exchange rate is the backbone of any economy in the world, whether developed or developing, where most countries adopted many policies, in order to ensure the stability of the exchange rate of the currency, because of its importance as a link between the local economy and the others ,And it contribute in the achievement of internal and external balance and despite the many different factors that affect it, but there is wide consensus on the effectiveness of the role of spending and the currency window in the exchange rate of the Iraqi dinar, especially in the Iraqi economy, effectiveness As the increase in government spending lead to an increase in the supply of money and increase domestic demand and high prices and therefore high inflation, which negatively affects the exchange rate of the Iraqi dinar, so the central bank intervenes through the window of currency in order to stabilize the exchange rate of local currency, Analysis of the relationship between expenditure and the currency window in the Iraqi economy for the period (004-2016) In order to establish the road map, the researcher tried to clarify the relationship mentioned above, The final result is that government spending negatively affects the value of the Iraqi dinar as a result of increased money supply and increased inflation caused by increased public spending. Therefore, the central bank intervenes through the currency window to sterilize the money supply by absorbing surplus cash flow (Iraqi dinar) During the pumping of more foreign currency and thus maintain the value of the Iraqi dinar exchange rate of the local currency, which has greatly affected the decline in inflation.